SIKAP MASYARAKAT NELAYAN KELURAHAN BONTANG BARU TERHADAP IMPLEMENTASI PROGRAM KAWASAN KONSERVASI PERAIRAN DI WILAYAH PESISIR DAN LAUT KOTA BONTANG - Harry Setiawan; Erwiantono; oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The purpose of this study were to determine the socio-economic characteristics, perception, motivation, and public attitudes towards regional coastal development program. Also to know the relationship between socioeconomic characteristic, perception and motivation with public attitudes of the Bontang Baru fisherman community toward the program implementation of water conservation area in Bontang City coral zone. Sampling method use census sampling with 54 respondents. The research has been conducted on Februari to Oktober 2017. Data analysis methods use descriptive qualitative method and quantitative analysis method with Rank Spearman’s correlation. The socioeconomic characteristics factors not related with attitudes of the Bontang Baru fisherman community toward the program implementation of water conservation area in Bontang City coral zone. The perception factor has realitionship to attitude on variabel of conseption conformity and the extention intensity toward the fisherman attitude. The motivation factor has realitionship to attitude on variabel the recognition of creadibility toward the attitudes of the Bontang Baru fisherman community toward the program implementation of water conservation area in Bontang City coral zone.